2010
DOI: 10.1002/nbm.1430
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance spectroscopy of the occipital cortex and the cerebellar vermis distinguishes individual cats affected with alpha-mannosidosis from normal cats

Abstract: A genetic deficiency of lysosomal alpha-mannosidase causes the lysosomal storage disease alphamannosidosis (AMD), in which oligosaccharide accumulation occurs in neurons and glia. The purpose of this study was to evaluate the role of magnetic resonance spectroscopy (MRS) in detecting the oligosaccharide accumulation in AMD. Five cats with AMD and eight age-matched normal cats underwent in vivo MRS studies with a single voxel short echo time (20 ms) STEAM spectroscopy sequence on a 4.7T magnet. Two voxels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Frozen tissues (~ 200–600 mg) were ground at liquid nitrogen temperature with 6% perchloric acid (3.25 ml per 1 g of tissue) using a method described previously . The homogenate was centrifuged at 13 000 rpm for 30 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Frozen tissues (~ 200–600 mg) were ground at liquid nitrogen temperature with 6% perchloric acid (3.25 ml per 1 g of tissue) using a method described previously . The homogenate was centrifuged at 13 000 rpm for 30 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…In vivo 1 H magnetic resonance spectroscopy (MRS) enables measurement of concentrations of cellular metabolites . However, in vivo MRS detection of lactate is difficult due to the overlap of the proton resonances emanating from the CH 3 ‐groups of lactate and CH 2 groups of lipids.…”
Section: Introductionmentioning
confidence: 99%
“…Feline models of a-mannosidosis showed abnormal apparent diffusion coefficients, hyperintensities in white matter on T 2 -weighted magnetic resonance images (Vite et al 2001(Vite et al , 2008, and MRS showed a broad signal in the 3.4-4.3 ppm region thought to represent mannose-rich oligosaccharides (Magnitsky et al 2010).…”
mentioning
confidence: 99%
“…Excess lysosomal material is microscopically exhibited by cellular swelling and can result in cellular dysfunction. 1,5 Lysosomal storage diseases can either be inherited or acquired. An inherited defect or deficiency in specific enzymes is responsible for the congenital form of this disease.…”
Section: Brief Communicationmentioning
confidence: 99%